2019
DOI: 10.1074/jbc.rev118.002958
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the multi-tRNA synthetase complex and its role in cancer

Abstract: Edited by Karin Musier-Forsyth Aminoacyl-tRNA synthetases (ARSs) are enzymes that ligate their cognate amino acids to tRNAs for protein synthesis. However, recent studies have shown that their functions are expanded beyond protein synthesis through the interactions with diverse cellular factors. In this review, we discuss how ARSs have evolved to expand and control their functions by forming protein assemblies. We particularly focus on a macromolecular ARS complex in eukaryotes, named multi-tRNA synthetase com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 84 publications
1
45
0
Order By: Relevance
“…Thus, it is reasonable to believe that besides combing PI3K-Akt inhibitors (Konstantinopoulos Several studies have also addressed aaRS's association with regulative pathways and processes. A predictive work raised the potential interaction between aaRSs (including LRS, DRS, RRS, IRS, KRS, QRS, EPRS) and MAPK/ PI3K-Akt pathways (Hyeon et al 2019). YARS was reported directly interacting with TRIM28/HDAC1 and sequestering HDAC1-mediated deacetylation on E2F1, thus enhances E2F1-mediated upregulation of homologous recombination (HR) factors and provides protection against DNA damage (Wei et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is reasonable to believe that besides combing PI3K-Akt inhibitors (Konstantinopoulos Several studies have also addressed aaRS's association with regulative pathways and processes. A predictive work raised the potential interaction between aaRSs (including LRS, DRS, RRS, IRS, KRS, QRS, EPRS) and MAPK/ PI3K-Akt pathways (Hyeon et al 2019). YARS was reported directly interacting with TRIM28/HDAC1 and sequestering HDAC1-mediated deacetylation on E2F1, thus enhances E2F1-mediated upregulation of homologous recombination (HR) factors and provides protection against DNA damage (Wei et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the upregulation of aaRSs, including YARS, was observed in several types of cancer (Guo et al 2010;Hsu et al 2019), while polymorphisms in aaRS genes were reported to be associated with breast cancer risk (He et al 2015). Emerging studies also implicated the involvement of aaRSs with multiple pathway networks through constituting the multi-tRNA synthetase complex (MSC) (Hyeon et al 2019) and raised the possibility of aminoacyl-tRNA synthetases as therapeutic targets against autoimmune diseases, rare diseases, and even cancer (Kwon et al 2019). Nevertheless, although abundantly exists and functions in all organisms, YARS's actual linkage with cancer remains unspecified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that AIMP3, which is specifically bound to MRS, relays the methionylated initiator tRNA to the initiator complex (Kang et al 2012). One aspect that is fundamentally clear is that in addition to the canonical tRNA charging activity, the MSC components are involved in several fundamental processes outside of translation such as transcription, cell-signaling and tumorigenesis (Hyeon et al 2019). For example, it has been shown that LeuRS interacts with the Target of Rapamycin (TOR) pathway, a highly conserved metabolic pathway involved in regulation of several key processes such as energy metabolism, protein synthesis, nutrient uptake or autophagy.…”
Section: The Multisynthetase Complexmentioning
confidence: 99%
“…The molecular size of the MSC, ∼1.0–1.2 MDa ( 14 , 22 , 25 , 26 ), is less than the ∼2 MDa, 60S eukaryotic large ribosomal subunit, however, given that RNA comprises at least half of the ribosome mass, the protein mass of the MSC is comparable to that of the 60S ribosome. Based on stoichiometric studies of the purified complex, and structural studies of purified constituents, the MSC is suggested to be a super-complex of two identical, symmetrically arranged sub-units, each containing a single copy of the constituents, with the exception of LysRS which is present as a dimer in each sub-unit (Figure 1B , adapted from ( 27 , 28 )). The sub-units are proposed to be joined by dimers of AspRS and the ProRS domain of GluProRS, and possibly by LysRS tetramers ( 20 ).…”
Section: Introductionmentioning
confidence: 99%